Fabricação e caracterização de diodo Schottky orgânico com arquitetura planar - Moisés, Lucas Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Usually organic polymeric diodes are made with a semiconductor layer placed between two electrodes in a sandwich-like architecture, where the electrodes are deposited on the surfaces of a polymeric semiconductor film. This methodology leads to two main problems: i) the polymeric film top surface is rough and irregular, resulting in non-uniform electric field into the device; ii) during the deposition of metallic electrode in the top surface polymeric film, by thermal evaporation, occurs the diffusion of metal atoms into the polymeric film, changing the material electronic structure. Thus, the metal-semiconductor junction is not well defined, which is essential for the production of good quality Schottky diode, which exhibits ideality factor close to the unity and low turn-on voltage. In order to avoid these two problems, in the present research was proposed to manufacture an organic diode with the semiconductor polymeric layer deposited over bimetallic (gold and aluminum) interdigitated electrodes. The doping of the active layer was performed by immersing the device in hydrochloric acid solution with pH 2 during different times in order to promote different doping levels of the semiconductor polymer. Was verified that the proposed diode, which exhibits well-defined metal-semiconductor junction, operates as a Schottky diode, with good ideality factor, 10 ± 3, and low turn-on voltage, 1,2 ± 0,2 V, in comparison with conventional organic polymeric diodes. Contrasting with the ideality factor and turn-on voltage, the diode rectification ratio was obtained as 7, a value lower than the expected for a good organic diode. Was also showed that the diode characteristics were dependent on the semiconductor polymer doping level, and that the diode characteristics were optimized with doping promoted by immersion in the acid solution for times longer than 50 s. Furthermore, as was showed that the diodes properties are dependent on the semiconductor...

Usualmente, diodos orgânicos poliméricos são fabricados com uma arquitetura do tipo sanduíche, onde os eletrodos são depositados nas faces de um filme semicondutor polimérico. Esta metodologia leva a dois problemas: i) a superfície superior do filme polimérico em geral é rugosa e irregular, resultando em um campo elétrico não uniforme no dispositivo; ii) durante a deposição do eletrodo na face superior no filme polimérico, por evaporação térmica de metais, ocorre a difusão de átomos metálicos para o interior do filme polimérico alterando, por esta razão, a estrutura eletrônica do material. Estes dois problemas acarretam na formação de junções metal-semicondutor que não são bem definidas, o que é indispensável para a produção de diodos Schottky de boa qualidade, com fator de idealidade próximo à unidade e baixa tensão de operação. Para evitar tais problemas, neste trabalho foi proposta a fabricação de diodos orgânicos onde o semicondutor foi depositado sobre uma estrutura de eletrodos interdigitados de ouro e alumínio. A dopagem da camada ativa se deu imergindo o dispositivo em ácido clorídrico com pH 2 durante diferentes tempos visando promover diferentes níveis de dopagem do polímero semicondutor. Foi demonstrado que os diodos propostos, por terem junções metal-semicondutor bem definidas, operam como diodos Schottky com bom fator de idealidade, 10 ± 3, e baixa tensão de operação, 1,2 ± 0,2 V, considerando-se o esperado para diodos orgânicos. Em contraposição aos valores do fator de idealidade e tensão de operação, o diodo apresentou fator de retificação em torno de 7, que é um valor a quem do esperado para um bom diodo orgânico. Demonstrou-se também que tais características são dependentes do nível de dopagem do material semicondutor e que foram otimizadas apenas quando o polímero semicondutor foi dopado com a imersão na solução ácida durante tempos superiores a 50 s. Como...
Keywords: Polímeros; Schottky, Diodos de barreira de; Eletrodos; Semicondutores